2020
DOI: 10.1016/j.cgh.2020.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gastrointestinal and Hepatic Manifestations of SARS-CoV-2 Infection in 892 Patients in Queens, NY

Abstract: S evere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an RNA virus responsible for coronavirus disease 2019 (COVID-19). 1,2 The virus enters cells via the angiotensin-converting enzyme 2 receptor, which is present in enterocytes in the ileum and colon. 3 Gastrointestinal (GI) manifestations include diarrhea, nausea, vomiting, and abdominal pain, and the prevalence of GI symptoms varies greatly, with a range between 2% and 57%. 4 In addition, abnormal liver chemistries are reported commonly. 4 As a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 6 publications
4
61
0
14
Order By: Relevance
“…There has only been one U.S.‐based study analyzing the relationship between elevated AST and ALT in conjunction with COVID‐19 outcome. ( 33 ) There have also been prior studies characterizing the effect of medical conditions on patients infected with SARS‐CoV2. ( 7,8,10 ) Advanced age, cardiopulmonary disease, and metabolic syndrome are all associated with risk of death and morbidity in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…There has only been one U.S.‐based study analyzing the relationship between elevated AST and ALT in conjunction with COVID‐19 outcome. ( 33 ) There have also been prior studies characterizing the effect of medical conditions on patients infected with SARS‐CoV2. ( 7,8,10 ) Advanced age, cardiopulmonary disease, and metabolic syndrome are all associated with risk of death and morbidity in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that different studies have adopted different criteria for what constitutes gastrointestinal symptoms. In some studies, gastrointestinal symptoms only included diarrhoea, nausea and vomiting 16 , 19 , 23 , whereas in others, symptoms such as loss of taste, abdominal pain and loss of appetite were also included 17 , 24 , 25 , 29 . For example, a multicentre study in China reported gastrointestinal symptoms, including diarrhoea (3.8%), nausea and vomiting (5%), as less common symptoms 11 , whereas one single-centre study in Baltimore, USA, reported gastrointestinal symptoms, including nausea, vomiting, diarrhoea, abdominal pain, anorexia, haematochezia, and loss of smell or taste, in more than 70% of patients with COVID-19 (ref.…”
Section: Gastrointestinal Symptoms In Covid-19mentioning
confidence: 99%
“…7 In a large retrospective study out of New York City, levels of aspartate aminotransferase (AST) were frequently higher than levels of ALT, suggesting that AST may be a useful indicator of COVID-19 infection. 8 A cholestatic pattern of injury, however, is rarely associated with COVID-19. 6,9 Other abnormalities in liver enzymes include elevations in gamma-glutamyl transferase (GGT), which, in one study, occurred in 13.6% of patients with COVID-19.…”
Section: ■ New Stressors In Covid-19mentioning
confidence: 99%
“…[13][14][15] Lopinavir/ritonavir, hydroxychloroquine (less commonly), azithromycin, and tocilizumab have also been associated with abnormal AST and ALT levels in this setting. 3,8 Although it is important to note that abnormal liver biochemistries are not a contraindication to using COVID-19 therapies, liver enzymes should be monitored regularly in all hospitalized COVID-19 patients. 1 A summary of recommendations for the evaluation of patients with abnormal liver enzymes and COVID-19 can be found in Table 1.…”
Section: ■ Approach To Elevated Liver Enzymesmentioning
confidence: 99%
See 1 more Smart Citation